Segmenting meeting and event management organizations based on business performance - Assaker, Guy (2016)
This study examines the characteristics and practices of small- and medium-sized meeting and event management organizations (MEMOs). Using data collected from 120 MEMOs in Australia, cluster analysis, chi-square, and Kruskal–Wallis were used to categorize and profile these organizations based on their performance levels. Significant differences were found between high-performing enterprises (HPE), average-performing enterprises (APE), and low-performing enterprises (LPE). These differences relate to a number of business and owner characteristics, including the age of the business, its legal structure, and the owners' level of entrepreneurial skills. These characteristics were used to both profile the HPEs and to identify factors that influence business performance. The findings from this study present implications for researchers in events and entrepreneurial studies as well as for policymakers aiming to support the sustainable development of the events management industry.